Assessment of Nutritional Status of Children With Congenital Heart Disease: A Comparative Study - Chinawa, Awoere T.; Chinawa, Josephat M.; Duru, Chika Onyinyechi; Chukwu, Bartholomew F.; Obumneme-Anyim, Ijeoma (Frontiers in Nutrition, 2021)
Background: Malnutrition poses a great burden to children in the tropics. However, this seems to be accentuated in children with congenital heart disease. Objectives: The present study is therefore aimed at determining the nutritional status of children with congenital heart disease and to compare them with those without congenital heart disease. Methods: This is a cross-sectional study, where congenital heart disease was diagnosed by means of echocardiograph. Anthro software was used to calculate Z scores for weight for age (WAZ), height for age (HAZ), and weight for height (WHZ). Body mass index (BMI) was calculated by the formula BMI = Weight (Kg)/height (M2). Results: The body mass index-for-age z-score (BAZ) and height/length-for-age z-score (HAZ) were calculated for both subjects and controls to determine their nutritional status. It was observed that 38.5% (112/291) of the subjects were wasted (BAZ < −2SD) compared to 6.25% (16/256) of the controls and the difference was statistically significant (χ2 = 81.2, p < 0.001). Stunting (height/length-for-age z-score < −2SD) was also observed in a greater proportion of subjects than controls as 37.8% (107/291) of subjects were stunted compared with 7.0% (18/256) of the controls (χ2 = 69.9, p < 0.001). The under-five subjects had more cases of malnutrition than the controls of same age group as illustrated in Table 6. Whereas 42.9% (96/224) of the under-five subjects were wasted, only 6.2% (12/192) of the controls were wasted. On the other hand, 4.2% (8/192) of the under-five controls were obese compared to 0.9% (2/224) of the subjects of similar age group. Conclusion: Children with congenital heart disease present with varying degrees of malnutrition that is worse compared with children without congenital heart disease. The impact of malnutrition is worse among children under the age of five. Wasting is more prevalent in children with cyanotic heart disease compared with those with acyanotic congenital heart disease. Overweight and obesity were notable features of malnutrition in children with congenital heart disease, but this is worse in children without congenital heart disease.